ANALYSIS OF COMPANY CAPABILITY USING 7S MCKINSEY FRAMEWORK TO SUPPORT CORPORATE SUCCESSION (CASE STUDY: PT X INDONESIA): ANALISA KAPABILITAS PERUSAHAAN DENGAN MENGGUNAKAN FRAMEWORK 7S MCKINSEY UNTUK MENDUKUNG KESUKSESAN PERUSAHAAN (STUDI KASUS: PT X INDONESIA) - Almira Devita Putri; Achmad Ghazali; Larasati Ahluwalia (Universitas muhammadiyah malang, 2021)
PT X Indonesia is a telecommunications company with a geographically focused division which operating in the province of West Java. PT. X Indonesia is currently undergoing a digital transformation to achieve its goal of